Application of the Decision Tree Method to Decision Makin in Using Trucking Services at A Freight Forwarding Company - Hidayat, Yusup Rachmat; Sya'aroh, Siti (Institut Ilmu Sosial dan Manajemen Stiami, 2023)
PT. Ricakusuma Lestari Abadi is a company operating in the freight forwarder sector by providing transportation services. Non-optimality and limited fleet capacity causes delivery activities to be inefficient in terms of time and cost. This research aims to determine the application of the decision tree method and determine the correct choice of decision making when using trucking services. Selecting trucking services using the Decision Tree method is a decision tool that uses a tree-shaped decision model. Meanwhile, for data analysis using the Decision Analysis method and to make it more effective and efficient, Information Technology is used in the form of Quantitative Method (QM) For Windows 5 software. The dependent variable in this research is the Decision Tree Method, and the independent variable is decision making. The data used in the research is field research and observation, direct observation at PT. Ricakusuma Lestari Abadi. The results of this research produced a minimum yield for Colt Diesel Engkel (CDE) trucks of IDR 270,000 for the Jakarta Area in the AKU trucking category and IDR 382,500 for Bekasi destinations in the ATT trucking category. And the minimum yield on a Colt Diesel Double (CDD) truck is IDR 315,000 for the Jakarta Area with the AKU trucking category and IDR 472,500 for Bekasi with the ATT trucking category.